Tantangan Pengembangan SDM Pendidikan dalam Menghadapi Kesenjangan Sosial dan Peningkatan Efektivitas Pembelajaran - Irnie Victorynie; Umdatul Mursiyah; Siti Apipah Zachroh Apipah (Attractive : Innovative Education Journal, 2024)
Education plays a very important role in helping individuals achieve a better quality of life and encouraging creativity. In this case, the existence of adequate educational facilities and qualified teaching staff have a very significant role. Therefore, the purpose of this paper is to identify the causal factors and propose solutions to overcome this inequality. This study was conducted using a qualitative approach, employing data collection techniques through literature reviews based on relevant journals. The findings revealed five main factors contributing to educational disparities in Indonesia. First, limited access to schools, particularly in remote areas. Second, insufficient educational facilities. Third, low motivation and poor quality of educators. Fourth, the high cost of education, which burdens household finances. Fifth, the low perception of the importance of education among communities. To reduce these disparities, several solutions are proposed, including optimizing the allocation of the national budget (APBN) to improve education quality, providing professional training for teachers to enhance their competencies, implementing scholarship programs and social work initiatives to develop students' skills, and conducting social awareness campaigns to emphasize the significance of education for younger generations.